“Phet Rose Apple” Identification using Image Processing - อ่วมศิริ, ศิริพร; กมลสันติโรจน์, สุวัจชัย; รัตนสัญญา, สรร (Journal of Applied Statistics and Information Technology, 2016)
Phet Rose Apple has a high impact on the economy of Thailand, which has high value of exports. The merchants however often sell other types of rose apple under this Phet Rose Apple name in the market, which results in customer’s hesitation to buy and having no confidence in buying them from the market. This causes continuously decreasing in sale volume of Phet Rose Apple, which has seriously affected lifestyle of farmers and the economy of Thailand. This paper proposes a method to identify Phet Rose Apple using image processing. Two significant features are extracted from the bottom area of rose apple, which are the area of petals's ratio and radius between each petal. The support vector machine then uses these features to identify Phet Rose Apple. The experimental results show that the proposed method can effectively identify Phet Rose Apple with high accuracy up to 97.78%. The results are then compared with the identification by the experts using statistical tests such as R2 = 0.96 which significantly indicates the impressive outcome of the proposed method